Effects of biocontrol agents on some soybean pathogens, diseases and yields - X.B. YANG, SHRISHAIL S. NAVI*, A.H. RAJASAB and (Indian Phytopathology, 2016)
Species of Trichoderma, Coniothyrium and Talaromyces biocontrol agents (BCA) have significantly (P